Therapeutic strategies in severe neuropsychiatric systemic lupus erythematosus: experience from a tertiary referral centre - F. De Leonardis; E. Galuppi; I. Farina; M. Padovan; A. Bortoluzzi; M. Govoni (PAGEPress Publications, 2012)
The management of neuropsychiatric systemic lupus erythematosus (NPSLE) still remains empirical and based on clinical experience due to the lack of randomized controlled trials. Objective: to report the experience accumulated in a single tertiary referral centre about treatment of severe cases of NPSLE patients and to discuss therapeutic strategies on the background of EULAR recommendations. Methods: retrospective analysis of all consecutive cases of severe NPSLE treated in our centre since 1990 to 2010, satisfying the 1999 ACR criteria. Results: among 633 SLE patients who consecutively attended our centre, 231 (36%) displayed at least one neuropsychiatric (NP) manifestation for a total of 408 events attributable to SLE. Thirty-one patients (4.8%), 27 females and 4 males, experienced 35 major NP events requiring immunosuppressive therapy (including 3 relapses and 1 new event). An aggressive immunosuppressive strategy was applied to those patients with an immune mediated inflammatory NP event and to those patients with an increased disease activity as judged by ECLAM and SLEDAI scores. Overall at the end of the therapy 74% of the patients reached clinical remission or significant improvement of their symptoms measured by mean SLEDAI (from 10.09±1.09 to 2.04±0.52, P<0.0001) and ECLAM (from 4±0.34 to 1.38±0.37, P<0.001) scores. Conclusions: the prevalence of NP involvement, described in our case series, is similar to those reported in literature as well as the treatment strategies applied. Nowadays, it is not possible to establish a standardized approach for each single NPSLE manifestation, and different therapeutic strategies must be tailored taking into account the most probable pathogenic mechanism involved, the general disease activity background, the co-morbidities, the type and the stage of the systemic involvement.